Integrating problem-based learning in e-lkpd: Enhancing problem-solving ability and adversity quotients - Rani, Thitra Padma; Sutiarso, Sugeng; Firdaus, Rangga (Universitas Islam Raden Intan Lampung, INDONESIA, 2024)
Background: Students' mathematical problem-solving ability and adversity quotient remain low, particularly in learning environments that lack contextual approaches. Problem-based learning (PBL) has proven effective in improving these skills, especially when supported by interactive technology such as E-LKPD.Aim: This study aims to develop a PBL-based E-LKPD that is valid, practical, and effective in enhancing students' problem-solving abilities and AQ.Method: The research employed the ADDIE development model with eighth-grade students from SMP Negeri in Banjar Baru as the subjects. The practicality sample consisted of 6 students selected through purposive sampling, while the effectiveness sample included 60 students selected through random sampling. Data were collected through observations, interviews, questionnaires, and problem-solving tests, then analyzed using descriptive statistics and t-tests.Result: PBL-based E-LKPD was deemed valid, with an average score of 87% from content experts and 85% from media experts. Its practicality was rated as excellent, with scores of 91% from both students and educators. An Independent Sample t-test on N-gain data indicated that the E-LKPD effectively improved students' mathematical problem-solving abilities and AQ (??? = 0.00 < ? = 0.05).Conclusion: The PBL-based E-LKPD has been proven valid, practical, and effective in enhancing students' mathematical problem-solving abilities and adversity quotient, making it a viable and innovative alternative in the learning process.